How China׳s urbanization impacts transport energy consumption in the face of income disparity. (December 2015) - Lin, Boqiang; Du, Zhili
Abstract: This paper estimates the transport energy consumption of 30 provinces in China from 1997 to 2011. By applying the STIRPAT model, the relationship between urbanization and transport energy consumption using control variables such as population, GDP per capita and the proportion of tertiary industry in GDP is investigated. Considering the disparities of income, the impacts of urbanization on transport energy consumption might be distinct. Therefore, this paper estimates the income threshold value and analyzes the effects of urbanization on transport energy consumption in the light of income differential using the panel threshold regression model. Based on the results, some policy suggestions are offered. Highlights: Estimate transport energy consumption in 30 provinces of China from 1997 to 2011. Use STIRPAT model to investigate the relationship between urbanization and transport energy consumption. Estimate the income threshold value, and analyzes the effects of urbanization on transport energy consumption in the difference of income using panel threshold regression model. Provide a reference for making reasonable energy conservation policies and emission reduction strategies.